Social media support group: Implementation and evaluation. Issue 4 (3rd April 2021) - Cooper, Haley; Reif, Susan; Shilling, Sara; Wilson, Elena
ABSTRACT: Lack of social support and perceived HIV-related stigma increase the risk of negative health-related outcomes among people living with HIV (PLWH). This study examines the social media use of PLWH participating in a behavioral health treatment program, and the association of participation in a "secret" Facebook group with improved client social support, education, and overall behavioral health treatment experience. Eighteen individuals participated in a survey and eight individuals participated in a focus group regarding their familiarity with technology and experience with using social media. Mixed-method analysis revealed that the majority of "secret" Facebook group participants thought that participation in the group improved overall personal wellbeing and perceived social support. However, lack of technology and social media experience and privacy concerns may have contributed to lower levels of participation with the "secret" Facebook group. A majority of participants who found Facebook difficult to use and/or had less technology experience were over the age of 50. Incorporating additional technology training for individuals who lack technology experience has the potential to improve clients' overall proficiency with technology and social media, as well as build confidence that could translate into an increased willingness to participate in a social media-based intervention.